2006
DOI: 10.1002/sia.2375
|View full text |Cite
|
Sign up to set email alerts
|

Optical microarray biosensing techniques

Abstract: Microarrays provide a powerful analytical tool for the simultaneous analyses of thousands of parameters, be they DNA or proteins, in a single experiment. However, a number of challenges continue to hinder the widespread application of microarray assays for analytical and diagnostic purposes. Advances in detection methods can help overcome some of these challenges by improving sensitivity and reliability in signal detection and by enabling real-time detection of binding events. Thus, the aim of this review is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
126
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(129 citation statements)
references
References 170 publications
(135 reference statements)
1
126
0
Order By: Relevance
“…One potential MEF application is to improve the sensitivity of DNA and protein microarrays, in which high density probes with spot sizes from 10 to 500 mm are immobilized on substrates with areas of several square centimeters. [35] Fluorescence is widely adopted for detection owing to its ultrahigh sensitivity and capabilities for multiple-probe labeling. Recently, use of SPR to lower the detection limit has become desirable to broaden its applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One potential MEF application is to improve the sensitivity of DNA and protein microarrays, in which high density probes with spot sizes from 10 to 500 mm are immobilized on substrates with areas of several square centimeters. [35] Fluorescence is widely adopted for detection owing to its ultrahigh sensitivity and capabilities for multiple-probe labeling. Recently, use of SPR to lower the detection limit has become desirable to broaden its applications.…”
mentioning
confidence: 99%
“…Recently, use of SPR to lower the detection limit has become desirable to broaden its applications. [35] To integrate our plasmonic material into commercial products, we demonstrated that our wrinkles can be easily patterned. In Figure 3e, discrete ''wrinkled flowers'' with diameters around 50 mm are shown to be well aligned.…”
mentioning
confidence: 99%
“…It is known that SERS has equal or in some cases a greater enhancement of Raman signal when compared to fluorescent markers and that SERS metal substrates produce spectral line widths which are 10-100 times narrower compared to fluorescence [64,318,319]. This means the technique can be used where high selectivity and multiplexing (targeting two analytes at once) is called for since the resolution between peaks will be well defined [320][321][322][323][324][325][326][327][328][329][330][331][332]. In addition, the short Raman scattering lifetime prevents photobleaching and quenching [312,323,324].…”
Section: Sers Immunoassaysmentioning
confidence: 99%
“…Solution based immunoassays overcome the slow diffusion kinetics and poor limit of detection (LOD) associated with conventional assays [73,319,320]. For example, the lung cancer carcinoembryonic antigen (CEA) was targeted using HGNs as a probe [325].…”
Section: Sers Immunoassaysmentioning
confidence: 99%
“…Similar to genome research, studying the characteristics of protein-protein interactions requires the ability to perform massively parallel analyses (Yu et al, 2006). Microarray technology is a promising method to provide an effective solution for simultaneous detection of various analytes in a single experiment (Bally et al, 2006). Microarrays are built by assembling a set of ligands onto a solid surface and are suitable for high-throughput analyses.…”
Section: Introductionmentioning
confidence: 99%